C63 PHENOTYPE – GENOTYPE RELATIONSHIP IN ARRHYTHMOGENIC CARDIOMYOPATHY. (18th May 2022) - Gueli, I; Alderotti, B; Todiere, G; Grigoratos, C; Modena, M; Botto, N; Vittorini, S; Vergaro, G; Giannoni, A; Aimo, A; Passino, C; Aquaro, G; et al.
Abstract: Background: Arrhythmogenic cardiomyopathy (ACM) is a primary disease of the myocardium with arrhythmic manifestations and fibro–fatty replacement either of the right (RV) or the left ventricle (LV) at the cardiac magnetic resonance (CMR). Over the last decade, different mutations in cardiac genes associated with heterogeneous phenotypes have been identified. Aim: To investigate the genotype–phenotype relationships in ACM patients. Firstly, the phenotypic expression was defined in definite mutation carriers. Secondly, the prognostic significance of mutations was assessed across different phenotypes. Methods: The study population included 281 patients with suspected ACM, based on family history, clinical and electrocardiographic evaluation, echocardiographic and CMR findings (Fig.1), studied at our Institution since 2012. All patients underwent genetic evaluation using Sanger sequencing and NGS of mutations in desmosomal (desmoplakin [DSP], plakophilin–2[PKP2], plakoglobin[JUP], desmoglein–2 [DSG2], desmocollin–2 [DSC2]) or non desmosomal genes. The composite endpoint included cardiac death, sustained and non–sustained ventricular tachycardia (VT), ventricular fibrillation (VF), appropriate defibrillator shock/antitachycardia pacing (ATP). Results: The genetic test was positive in 113 patients (40%), 82 (73%) for desmosomal genes (41 DSP, 15 DSG2, 15 PKP2, 5 JUP, 6 DSC2), and 31 (27%) for non–desmosomal genes (4 titin, 2 TMEM 43, 2 lamin A/C, 23 others). Gene–positive compared to gene–negative (n = 168, 60%) patients showed a higher prevalence of LV ejection fraction (EF)<50% (14%vs.6%, p<0.011), LV and RV LGE (62%vs.46%, p < 0.001, 20%vs.12%, p<0.02), RV dilatation (27%vs.17%, p<0.041) (Table 1). DSG2 mutations were associated mainly to biventricular (7/15, 46%) or RV involvement (4/15, 26%), while DSP mutations to LV involvement (24/41, 58%). During a median 36–month follow–up (IQ.range 12–56), 55 patients (19%) experienced the composite endpoint (35 non–sustained VT; 11 sustained VT – 3 ATP, 1 defibrillator–shock–; 9 VF, all treated by defibrillator–shock). At Kaplan–Meier analysis, DSP mutations were associated with the worst prognosis (Fig. 3). Conclusion Diverse genotypes were differently associated with LV dysfunction/LGE, RV dilatation/LGE. DSP mutations were associated with higher arrhythmic risk. Genetic screening may result in a better risk stratification, useful for clinical decision–making.